Study In Silico of the Activity of Bioactive Compounds from Cinnamon (Cinnamomum verum) Bark as Anti-inflammatory - Prima Gita Islami Islami; R Susanti (Journal of Science and Technology Research for Pharmacy, 2024)
Cinnamon bark (Cinnamomum verum) contains various bioactive compounds that can be used in drug development, one of which is anti-inflammatory. Inflammation is the body's defense response to the occurrence of an injury from objects unknown to the body, such as bacterial infections, trauma, autoimmune, viruses and toxins. The purpose of this study was to determine the content of bioactive compounds in cinnamon bark. This research method was carried out using the Dr. Duke's Phytochemical database. Duke's Phytochemical database to collect bioactive compounds in cinnamon bark, PubChem to download the ligand structure of bioactive compounds, PASS (Prediction of Activity Spectra for Substance) Online for screening the anti-inflammatory activity value of bioactive compounds, SEA and Swiss Target Prediction are used to determine the target protein, STRING is used to analyze the interaction between target proteins, Cytoscape is used to predict tissue topology, Pyrex is used for molecular docking, and Biovia Discovery Studio is used to visualize docking results. There are 16 cinnamon bark compounds that have a Pa value > 0.5. Based on the docking results, compounds that have a Pa value> 0.5. Based on docking results, beta caryopyhllene, caryopyhllene, fatty acid, and isocaryopyhllene compounds have PPARA activator mechanism with binding affinity of -7.4 kcal/mol, -7.9 kcal/mol, -7.8 kcal/mol, and -5.6 kcal/mol. Caffeic acid compounds have an MMP-9 activator mechanism with a binding affinity of -5.7 kcal/mol. Visualization of docking results shows that isocaryopyhllene and caffeic acid compounds have similar interactions and amino acid residues with control drugs so that they can be used as anti-inflammatory agents.